integration by parts example 5
HTML-код
- Опубликовано: 8 фев 2025
- We integrate: (x ^ 2)e^(- 3x), by integration by parts, taking u=x^2, in addition to dv=e^(-3x)dx. Then, we apply again integration by parts in the resulting integral, taking: u=x, with dv=e^(- 3x)dx.
Excelente! Gracias
Este si sabe utilizar bien su barbita ❤
Muchas gracias profesor, saludos
Muchas gracias 😊
Gracias.
muchas gracias profe
Gracieas,amigo im Italian.😅 nothing yet talking...😅❤🎉
Gracias buena noche
Graicas por ver videos en este canal.